Ottoman policy towards Yemen during the first half of the nineteenth century - جبور علاء الدين (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
The research deals with the policy of the Ottoman Empire towards Yemen in the first half of the nineteenth century AD. This policy was represented by the Ottoman Empire’s efforts to eliminate the Wahhabi movement in the Arabian Peninsula through the Egyptian governor Muhammad Ali Pasha, and the resulting repeated campaigns to the regions of northern Yemen. , In addition to the impact of the Ottoman disputes with the governor of Egypt on the political situation in Yemen until the Egyptian army left it in 1840 AD, in addition to the state’s efforts to impose its actual and direct control in Yemen through its campaign there in 1849 AD.